2008
DOI: 10.1080/13697130802232500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fulvestrant alone or combined with different steroids in human breast cancer cellsin vitro

Abstract: Our study demonstrated that fulvestrant, an ER antagonist used in the treatment of ER-positive breast cancer, combined with E2 and DHD or in combination with tibolone, is not compromised in its efficacy in inducing apoptosis in ER-positive breast cancer cell lines in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Statistically significant differences ( p < 0.05) between the ER + cell line and the two ER – cell lines are indicated in these graphs by italic letters A and N . In line with previous literature, the pure antiestrogenic drug fulvestrant significantly reduced cell growth of the ER + cells while having little or no impact on the growth of either of the ER – cell lines . 4-Hydroxytamoxifen, the active metabolite of tamoxifen, specifically inhibited only the ER + cell line at 10 –8 M to 10 –6 M, with both ER + and ER – cell lines being affected at higher concentrations.…”
Section: Biological Results and Discussionsupporting
confidence: 90%
“…Statistically significant differences ( p < 0.05) between the ER + cell line and the two ER – cell lines are indicated in these graphs by italic letters A and N . In line with previous literature, the pure antiestrogenic drug fulvestrant significantly reduced cell growth of the ER + cells while having little or no impact on the growth of either of the ER – cell lines . 4-Hydroxytamoxifen, the active metabolite of tamoxifen, specifically inhibited only the ER + cell line at 10 –8 M to 10 –6 M, with both ER + and ER – cell lines being affected at higher concentrations.…”
Section: Biological Results and Discussionsupporting
confidence: 90%
“…As genistein‐mediated PON1 induction was inhibited by the oestrogen‐receptor antagonist fulvestrant, it may be hypothesized that the induction of PON1 because of genistein could be partly be via an oestrogen‐receptor‐dependent signal transduction pathway. However, it needs to be taken into account that the fulvestrant concentration, as used in our Huh7 cell culture studies, was manifold higher than those previously reported in the literature . Furthermore, we found putative AhR binding sites in the PON1 promoter in silico .…”
Section: Discussionmentioning
confidence: 99%
“…To answer the research questions, an epidemiological study and in vitro research were carried out. 26,27 …”
mentioning
confidence: 98%